(3eLehY COHjs - (3eLghds
(3ChdgG (B:s
(3SCdJ GdbQi hGdLhO Cf MddJeG hCjf ebQ GdeLO hGdCKQGJ s
(3BNQgG (B:s
(3hbO dPfG HLfGHce, hdG Zfi dfG Yf HQcGJce hHGHcehCOGe CYdGece HGdYR hGdaJM hEPG GdZeGFoe CNdaJ aj QaOgG CZfGc ef ZjK GdSeGA eMeO s
(3HgG fXGe GdJYbjHIs
(3ajg bUGFO hecGJHGJ aj GdeOjM (B- (3aj YgO GdOhdI GdYdhjIs
(3JHUQI GdYfhGf (B:s
(3LeY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdCOHs